Resepsi Moderasi Beragama Pada Masyarakat Pesantren (Studi Living Qur’an di Pondok Pesantren Attaqwa Bekasi) - Huda, Ade Naelul; Fitriana, Muhammad Azizan; Sudrajat, Jajat (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
This study aims to see how the pesantren community in Attaqwa Bekasi Islamic Boarding School perceives the values of religious moderation. Pesantren is considered as a small miniature of religious attitudes and perspectives in Indonesia so it is important and interesting to see how the response and response of the pesantren community to religious moderation; which is a concept related to the religious attitude of the Indonesian nation which was popularized massively by the Ministry of Religious Affairs. This research uses qualitative methods in the form of field research, data collection using interview and observation techniques and then analyzed using a descriptive analysis approach, the indicators used are four indicators of Religious Moderation carried by the Ministry of Religious Affairs, namely national commitment, tolerance, non-violence and respect for local culture. The results showed that the value of religious moderation has been understood by all elements of Islamic boarding schools, moderation is understood through wasathiyatul Islam which is considered in line with Islam. The Attaqwa Islamic Boarding School also recognizes Pancasila as the final foundation of the state and considers it not to conflict with the teachings of Islam. Attaqwa Islamic Boarding School has also implemented tolerant behavior and respects differences. Even so, students are still given the strengthening of creed and guidance on the correct application of tolerance in the Islamic view. The Attaqwa Islamic Boarding School upholds the rejection of violence, stressing that this attitude has been exemplified by its founder, KH. Noer Alie who fosters society regardless of religion, race, social status and background. Attaqwa Islamic Boarding School is known as one of the pesantren that accepts and even practices a lot of local culture in ubudiyah and muamalah. This acceptance of local culture makes Attaqwa Islamic Boarding School an accepted and even inherent in the community.